Banks' Adjustment to Basel III Reform : A Bank-Level Perspective for Emerging Europe - Andrle, Michal; Tomaik, Vladimir; Vlcek, Jan. (Washington, D.C. : International Monetary Fund, 2017)
The paper seeks to identify strategies of commercial banks in response to higher capital requirements of Basel III reform and its phase-inches It focuses on a sample of nine EU emerging market countries and picks up 5 largest banks in each country assessing their response. The paper finds that all banking sectors raised CAR ratios mainly through retained earnings. In countries where the banking sector struggled with profitability, banks have resorted to issuance of new equity or shrunk the size of their balance sheets to meet the higher capital-adequacy requirements. Worries echoed at the early stage of Basel III compilation, namely that commercial banks would shrink their balance sheet by reducing their lending to meet stricter capital requirements, did materialize only in banks struggling with profitability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet